2010
DOI: 10.1128/ec.00015-10
|View full text |Cite
|
Sign up to set email alerts
|

Downregulation of an Entamoeba histolytica Rhomboid Protease Reveals Roles in Regulating Parasite Adhesion and Phagocytosis

Abstract: Entamoeba histolytica is a deep-branching eukaryotic pathogen. Rhomboid proteases are intramembrane serine proteases, which cleave transmembrane proteins in, or in close proximity to, their transmembrane domain. We have previously shown that E. histolytica contains a single functional rhomboid protease (EhROM1) and has unique substrate specificity. EhROM1 is present on the trophozoite surface and relocalizes to internal vesicles during erythrophagocytosis and to the base of the cap during surface receptor capp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
98
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 65 publications
(107 citation statements)
references
References 58 publications
9
98
0
Order By: Relevance
“…The G3 parasites were a gift from Dr. David Mirelman, and G3-based secondary gene silenced parasites were generated by transfection of G3 parasites with psAP-2/5ЈSTIRP plasmid or psAP-2/3ЈSTIRP plasmid (see "Plasmid Construction for EhSTIRP Gene Silencing"). EhROM(KD) parasites were generated as described previously (26), with separate cultures having been maintained with or without drug at 2 g/ml G418. The N-terminal Myc-tagged EhAGO2-2 parasites were previously generated (20) and have been maintained at 24 g/ml G418.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The G3 parasites were a gift from Dr. David Mirelman, and G3-based secondary gene silenced parasites were generated by transfection of G3 parasites with psAP-2/5ЈSTIRP plasmid or psAP-2/3ЈSTIRP plasmid (see "Plasmid Construction for EhSTIRP Gene Silencing"). EhROM(KD) parasites were generated as described previously (26), with separate cultures having been maintained with or without drug at 2 g/ml G418. The N-terminal Myc-tagged EhAGO2-2 parasites were previously generated (20) and have been maintained at 24 g/ml G418.…”
Section: Methodsmentioning
confidence: 99%
“…A single cloned parasite from this transfectant line is named G3 (24). Importantly, it was later found that a second unrelated gene of interest could be transcriptionally silenced by transfecting G3 with a plasmid in which a second gene was cloned directly after the ap-a promoter fragment (23,25,26). The resulting secondary gene silencing is also inheritable and can be maintained after removal of the plasmid.…”
mentioning
confidence: 99%
“…In resting conditions, EhROM1 is located both at the parasite surface and in internal punctate structures but upon erythrophagocytosis it relocates to internal vesicles [68]. EhROM1 knockdown leads to a defect in parasite adhesion to healthy cells as well as a generalized phagocytosis defect that are attributed to independent functions of the rhomboid protease, perhaps related to different substrates [69]. Although EhROM1 can cleave in vitro the parasite adhesin Gal/GalNAc lectin, there was no change in the expression or localization of this protein in cells depleted of the rhomboid [69].…”
Section: Entamoebamentioning
confidence: 99%
“…In vivo: unknown Entamoeba histolytica EhROM1 Parasite surface and internal punctuate structures (resting conditions) Internal vesicles (erythrophagocytosis) [68] In vitro: EhGal/GalNAc lectin [68] Parasite adhesion to healthy cells Phagocytosis [69] In vivo: unknown Phylogenetic analysis of Kinetoplastidiae ROMs. The tree is based on neighbour-joining-distance analysis.…”
Section: Unknownmentioning
confidence: 99%
“…Rhomboid proteases are known virulence factors that function in adhesion and phagocytosis of the host cells and thus have a well-studied role in host-parasite interactions (46)(47)(48). By fusing 152-Trigger to full-length myc-tagged ROM1 (1,008-bp coding region), the 152-Trigger-EiROM construct was generated (Fig.…”
Section: Figmentioning
confidence: 99%